Persecution in 1 Peter differentiating and contextualizing early Christian suffering - Williams, Travis B. 1980- (Leiden Boston Brill, 2012)
Preliminary Material -- 1. Introductory Matters -- 2. Social Conflict in Social-Psychological Perspective -- 3. The Geographical Setting of 1 Peter -- 4. The Addressees of 1 Peter -- 5. Conflict Management in Roman Anatolia -- 6. The Legal Status of Christians in the Roman World -- 7. The Cause(s) of Conflict in 1 Peter -- 8. The Form(s) of Conflict in 1 Peter -- Conclusion -- 1. Suffering and the Unity of 1 Peter -- 2. Roman Annexation of Asia Minor -- 3. Cities of First-Century CE Anatolia -- 4. Ancient Economics in Recent Discussion -- Bibliography -- Index of Modern Authors -- Index of Subjects -- Index of Ancient Sources.
In Persecution in 1 Peter , Travis B. Williams offers a comprehensive and detailed socio-historical investigation into the nature of suffering in 1 Peter. While interpreters commonly portray the conflict situation addressed by the epistle as \'unofficial\' persecution consisting of discrimination and verbal abuse, Williams demonstrates the inadequacy of this modern consensus by situating the letter against the backdrop of conflict management in first-century CE Asia Minor. Drawing on a wide range of historical evidence and on modern social-psychological perspectives, this work reconstructs the conflict situation of the Anatolian audience and offers important insights regarding the legal culpability of Christians following the Neronian persecution, the roles of local and provincial authorities in the judicial process, and the variegated conflict experiences of different socio-economic groups within the Christian communities
Includes bibliographical references (p. [387]-446) and indexes
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Persecution -- Biblical teaching; Persecution -- History -- Early church, ca. 30-600; Suffering -- Biblical teaching; Conflict Management -- Biblical teaching; Social conflict in the Bible; Persecution -- Biblical teaching; Persecution -- History -- Early church, ca. 30-600; Suffering -- Biblical teaching; Conflict Management -- Biblical teaching